Human P2Y11 Expression Level Affects Human P2X7 Receptor-Mediated Cell Death - Dreisig, Karin; Sund, Louise; Dommer, Maja Wallentin; Kristensen, Nikolaj Pagh; Boddum, Kim; Viste, Rannveig; Fredholm, Simon; Odum, Niels; Jäättelä, Marja; Skov, Søren; Kornum, Birgitte R. (Frontiers in Immunology, 2018)
Adenosine triphosphate (ATP) is known to induce cell death in T lymphocytes at high extracellular concentrations. CD4+ and CD8+ T lymphocytes have a differential response to ATP, which in mice is due to differences in the P2X7 receptor expression levels. In contrast, we observed that the difference in human CD4+ and CD8+ T lymphocyte response towards the synthetic ATP-analogue BzATP is not explained by a difference in human P2X7 receptor expression. Rather, the BzATP-induced human P2X7 receptor response in naïve and immune-activated lymphocyte subtypes correlated with the expression of another ATP-binding receptor: the human P2Y11 receptor. In a recombinant expression system, coexpression of the human P2Y11 receptor counteracted BzATP-induced human P2X7 receptor-driven lactate dehydrogenase (LDH) release (a marker of cell death) and pore formation independent of calcium signalling. A mutated non-signalling human P2Y11 receptor had a similar human P2X7 receptor-inhibitory effect on pore formation thus demonstrating that the human P2X7 receptor interference was not caused by human P2Y11 receptor signalling. In conclusion, we demonstrate an important species difference in the ATP-mediated cell death between mice and human cells and show that in human T lymphocytes, the expression of the human P2Y11 receptor correlates with human P2X7 receptor-driven cell death following BzATP stimulation.